DETECÇÃO DE RESPOSTA SOROLÓGICA CONTRA MYCOPLASMA EM AVES DE CRIATÓRIOS DE “FUNDO DE QUINTAL” PRÓXIMOS A EXPLORAÇÕES COMERCIAIS DO ESTADO DE SÃO PAULO - Buchala, F.g.; Ishizuka, M.m.; Mathias, L.a. [UNESP]; Berchieri, A. [UNESP]; Castro, A.g.m.; Cardoso, A.l.s.p.; Tessari, E.n.c.; Kanashiro, A.m.i. (Instituto Biológico, 2022)
This investigation aimed to demonstrate the occurrence of serological reactions to Mycoplasma gallisepticum and Mycoplasma synoviae in domestic backyard poultryfor self consumtion located next to parent flocks in the State of São Paulo. Fifteen backyard flocks around 3 parent flocks officially recognized as free from MG and MS were selected.Sera from 406 chickens were researched on antibodies anti MG and MS, by means of plate agglutination test. The frequencies found were 73% and 100% of flocks with chickens reacting to the antigens of MG and MS, respectively. The frequencies of reacting chickens were 30.3% and 40.6% for the antigens of MG and MS, respectively. The results showed that the aetiological agents studied are widespread among the backyard flocks, posing a constant risk for the commercial poultry flocks, which need to adopt and keep good biosecurity practices to preserve their sanitary status.

Pesquisou-se anticorpos anti Mycoplasma gallisepticum (MG) e Mycoplasma synoviae (MS) nas populações de aves de produção não tecnificada e com finalidade de subsistência, em propriedades rurais em áreas geográficas próximas a granjas de reprodutoras (matrizeiros) do Estado de São Paulo. Foram selecionadas quinze criações vizinhas a 3 granjas de matrizes, consideradas livres de MG e MS. Soros sanguíneos de 406 galinhas foram estudados quanto a presença de anticorpos anti MG e MS. A avaliação foi realizada pela técnica de soroaglutinação rápida em placa. As freqüências de positividade encontradas foram de 73% e 100% das aves aos antígenos de MG e MS, respectivamente. As ocorrências observadas de aves sororreagentes foram de 30,3% e 40,6% para os antígenos de MG e MS, respectivamente. Os resultados indicaram que MG e MS estão amplamente difundidos nas criações informais de aves de “fundo de quintal”, colocando em risco constante os criatórios de exploração industrial, os quais necessitam adotar e manter boas práticas de biossegurança para preservar a integridade sanitária dos plantéis.
DETECTION OF SOROLOGICAL RESPONSE AGAINST MYCOPLASMA IN DOMESTIC BACKYARD POULTRY AROUND COMERCIAL POULTRY FLOCKS IN THE STATE OF SÃO PAULO, BRAZIL
Keywords: Biosecurity; epidemiology; infections; poultry healther; micoplasmoses; Biossegurança; epidemiologia; infeccões; saúde das aves; micoplasmose